D Dinamika Budaya Jawa Dalam Konteks Sedekah Bumi Tinjauan Maqasid Syariah Perspektif Syekh Izzudin Bin Abdissalam - Ahmad Muhammad Usama; M. Ali Khumaini (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2026)
Abstrac This study examines the dynamics of Javanese culture within the tradition of sedekah bumi (earth offerings), highlighting the perspective of Maqasid al-Shariah by Sheikh Izzuddin bin Abdissalam as presented in the book Qawa'id al-Ahkam fi Mashalih al-Anam. The primary issue explored is how sedekah bumi can be understood within the framework of Islamic law and the significance of cultural syncretism for the continuity of religious values. This research was conducted using a qualitative approach based on a literature review, analyzing the primary texts of Sheikh Izzuddin bin Abdissalam along with supporting literature related to syncretism and the interaction between religion and local culture. The results indicate that although sedekah bumi is rooted in local culture, it can be accommodated within the Maqasid al-Shariah framework due to its inherent public welfare values. An inclusive Sufi approach transforms this practice into an effective medium for da’wah without compromising monotheistic principles (tauhid). This study contributes to the discourse on Islam Nusantara and provides practical insights for religious institutions in strengthening tolerance and cultural harmony within pluralistic societies. Keywords: Syncretism, Earth Alms, Maqasid Sharia, Sufism, Islam Nusantara, Sheikh Izzudin bin Abdissalam